Suplementasi Sari Belimbing Wuluh (Averrhoa bilimbi L.) dalam Air Minum terhadap Produktivitas Telur Puyuh: Supplementation of Averrhoa bilimbi L. Juice in Drinking Water on Performance and Physical Quality of Quail Egg - Lylya Wahyuni; M R Ramdani; N O Imama; V E Larasati; A R Fahmi; W Hermana (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2020)
Supplementation of Averrhoa bilimbi L. juice which contains vitamin C and organic acid in drinking water has been proposed to reduce the effect of heat stress on the quail layer. So this is expected to increase the productivity of quail and their egg quality. The aim of this research was to determine the effect of A. bilimbi juice supplementation in quail drinking water on quail performance, physical quality of egg, and egg yolk antioxidant level. Two hundred and forty birds aged 4-5 weeks were maintained for 42 days. A Completely Randomized Design was used in this study with 4 treatments. Each treatment has 4 replications and 15 quails in each replications. Addition of Vita Chick (P0) to the drinking water was used as a positive control. The treatments given were the addition of A. bilimbi extract with different levels of 0% (P1), 2.5% (P2), and 5% (P3) respectively. The variables observed were quail performance, physical egg quality, and egg yolk antioxidant levels. The results showed that the physical quality of quail eggs obtained were the weight of albumen and egg shells did not different all treatments. The addition of A. bilimbi juice in drinking water has affected on the weight and percentage of albumen, eggshell, and Haugh Unit. The addition of 2.5% of A.bilimbi juice (P2) had the lowest feed conversion ratio (FCR). However it showed the highest Haugh Unit number of the egg. There was no different effect of the highest dose of A. bilimbi juice (5%, P3) on the egg yolk antioxidant activity and capacity (41.54% and 23.91 ppm respectively). It was concluded that supplementation of A. bilimbi juice in drinker water could changed to antistress drug commercial.